Study of the Influence of Homocysteine and Vitamin D Metabolism on the Development of Destructive Vascular Wall Processes - Nikonenko, O. S.; Nikonenko, A. O.; Chmul, K. O.; Osaulenko, V. V. (Ukrainian Journal of Cardiovascular Surgery, 2020)
To date, it has been established that in the progression of cardiovascular (CV) disorders, an increase in the level of homocysteine (HC) and hypovitaminosis D play an important role. According to the latest recommendations, the modern clinician should consider risk factors not as a diagnostic sign, but as a prognostic, contributing factor, which to some extent can lead to destructive changes in the vascular wall. The aim. To study the morphological changes of the vascular wall depending on the degree of hyperhomocysteinemia and hypovitaminosis D. Materials and methods. We analyzed data from 54 patients who, in addition to determining the level of HC and vitamin D, underwent morphological studies of fragments of the great saphenous vein and aorta. Samples were obtained during coronary artery bypass grafting. Depending on the degree of hyperhomocysteinemia and the level of vitamin D, the patients were divided into 3 groups. Results. Morphological examination of the great saphenous vein and aorta showed normal structure of the vascular wall in patients with normal levels of HC and vitamin D (78.5% and 71.4%, respectively). Patients from the groups 2 and 3 with hyperhomocysteinemia had more pronounced changes in the venous wall, regardless of the level of vitamin D. These data suggest a probable association of HC levels with the changes in the vascular wall. It was also noted that the patients of group 3 had more pronounced inflammatory infiltration of the vascular wall. Conclusions. Hyperhomocysteinemia and hypovitaminosis D are independent predictors of CV disorders and have a detrimental effect on the vascular wall and blood coagulation system, creating conditions for the progression of atherosclerosis. The higher is the level of HC, the more pronounced are morphological changes in the vascular wall of the vein, leading to hypertrophy of all layers, regardless of the level of vitamin D.